1996
DOI: 10.1103/physrevb.54.7216
|View full text |Cite
|
Sign up to set email alerts
|

X-ray magnetic scattering study of three-dimensional magnetic order in the quasi-one-dimensional antiferromagnetNd2BaNiO

Abstract: We report a resonant x-ray-scattering determination of order parameter of the Nd sublattice in the quasione-dimensional antiferromagnet, Nd 2 BaNiO 5 . We find that long-range order develops below T N ϭ48 K, and that the staggered magnetization continues to grow down to Tϭ10 K. This is in contrast with the behavior of the Ni sublattice, which quickly saturates, as determined previously by neutron-scattering. We find this behavior is modeled well by a self-consistent mean-field theory. Large resonant enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
34
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
8
34
0
Order By: Relevance
“…This three dimensional antiferromagnetic matrix generates an effective staggered magnetic field on the Ni 2+ chains whose intensity can be tuned by varying the temperature below T N . In this way, experiments have been able to investigate the effects of a staggered field on the Haldane gap, the staggered magnetization and the susceptibility 31,32 . Stimulated by these experiments, few analytical and numerical studies attempted a theoretical analysis of spin chains in staggered fields by use of semiclassical mappings 12,14 and DMRG 33 .…”
Section: Heisenberg Model In An External Fieldmentioning
confidence: 99%
“…This three dimensional antiferromagnetic matrix generates an effective staggered magnetic field on the Ni 2+ chains whose intensity can be tuned by varying the temperature below T N . In this way, experiments have been able to investigate the effects of a staggered field on the Haldane gap, the staggered magnetization and the susceptibility 31,32 . Stimulated by these experiments, few analytical and numerical studies attempted a theoretical analysis of spin chains in staggered fields by use of semiclassical mappings 12,14 and DMRG 33 .…”
Section: Heisenberg Model In An External Fieldmentioning
confidence: 99%
“…The orthorhombic crystal structure of R 2 BaNiO 5 compounds is discussed in great detail elsewhere [16] and we only note here that the S = 1 Ni 2+ chains run along the a axis of the crystal (Ni-Ni spacing a = 3.85Å), with the R 3+ sites positioned in-between these chains. The Néel temperature for Nd 2 BaNiO 5 is T N = 48 K. Long range magnetic ordering gives rise to magnetic Bragg reflections of the type ( 2 ), with m, k and n integer [17,18]. The Ni 2+ moments are confined in the (a, c) crystallographic plane and are aligned roughly along the c axis [17,19].…”
mentioning
confidence: 99%
“…3 The Ni +2 and Nd +3 moments are coupled antiferromagnetically along the chain ('a' axis) but coupled ferromagnetically along 'b' axis. The Ni moments start to order antiferromagnetically below 48 K, 9 and reaches its saturation value around 35 K with decreasing T. The Nd moments also orders antiferromagnetically below 48 K, but the magnitude of its moment increases relatively slowly with decreasing T. 3 The magnetic susceptibility (χ) shows a broad maximum around 26 K which was attributed to the depletion of the higher-lying level of the Kramers doublet, split by Nd-Ni magnetic interactions. 10 Inelastic neutron scattering studies revealed clear evidence for one-dimensional gap excitations.…”
mentioning
confidence: 99%